Use of thoracic ultrasound on Scottish dairy cattle farms to support the diagnosis and treatment of bovine respiratory disease in calves. (23rd September 2021) - Baxter‐Smith, Katharine; More, James; Hyde, Robert
Abstract: Background: Bovine respiratory disease (BRD) is common in cattle youngstock on UK dairy farms. The current diagnostic methods lack sensitivity and specificity. Thoracic ultrasound (TUS) is a relatively new BRD diagnostic tool with increased accuracy. Method: Data were collected from TUS examinations of 347 calves on Scottish dairy farms and compared to farmer BRD treatment rates. A calf health scoring tool was used to collect information on youngstock health and management on these farms. Results: Of 347 ultrasonographic examinations, 53 (15.3%) were classified as abnormal and 294 (84.7%) as normal. Of the 53 calves classified as abnormal, only 13 (24.5%) were treated by the farmer; however, of the 294 classified as normal, 22 (7.5%) were treated. Conclusion: The results indicated farmers were misdiagnosing BRD in youngstock. Use of TUS on UK farms may improve diagnostic rates and accuracy, reduce the unnecessary use of antimicrobials and demonstrate the value of preventive healthcare programmes.